2020
DOI: 10.3390/ijms21082984
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Identification of M35 Family Metalloproteases in Rhizoctonia cerealis and Functional Analysis of RcMEP2 as a Virulence Factor during the Fungal Infection to Wheat

Abstract: Rhizoctonia cerealis is the causal pathogen of the devastating disease, sharp eyespot, of the important crop wheat (Triticum aestivum L.). In phytopathogenic fungi, several M36 metalloproteases have been implicated in virulence, but pathogenesis roles of M35 family metalloproteases are largely unknown. Here, we identified four M35 family metalloproteases from R. cerealis genome, designated RcMEP2–RcMEP5, measured their transcriptional profiles, and investigated RcMEP2 function. RcMEP2-RcMEP5 are predicted as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…The metalloprotease is also involved in the regulation of pathogenicity. Previous studies have shown that FocM35_1, RcMEP2-RcMEP5, and MrM35-4 played important roles in pathogenicity ( 25 , 26 , 32 ). After gene deletion, the pathogenicity of deletion mutants was significantly decreased compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metalloprotease is also involved in the regulation of pathogenicity. Previous studies have shown that FocM35_1, RcMEP2-RcMEP5, and MrM35-4 played important roles in pathogenicity ( 25 , 26 , 32 ). After gene deletion, the pathogenicity of deletion mutants was significantly decreased compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Avr-Pita of the M35 family of Magnaporthe grisea proved to be an effector protein interacting with Pi-ta in plant cells to trigger host defense response ( 24 ). Rhizoctonia cerealis M35 family RcMEP2 and an entomopathogenic fungus Metarhizium anisopliae M35-4 had secretory activity and played a role in host infection as pathogenic factors ( 25 , 26 ). Previous studies have shown that V. dahliae VdASPF2 secreted protein with M35 family conserved domain.…”
Section: Introductionmentioning
confidence: 99%
“…The picture of His-TF-RcMEP2 at 60 min was confused by L.J.P. because the sample container marker was blurred [ 1 ]. Thus, Figure 8 should be replaced with the following figure ( Figure 1 ).…”
mentioning
confidence: 99%
“…Curiously, M35s may also play important roles in mycoparasitic fungi during interactions with their host or prey. For example, in the mycoparasite fungus Trichoderma guizhouense, the disruption of an M35 gene (NMP1) led to a loss of ability to inhibit the in vitro growth of plant-pathogenic fungi, such as Atheria rolfsii, Fusarium oxysporum, and Sclerotinia sclerotiorum (Zhang et al, 2016) A body of evidence suggests that M35s act as crucial virulence factors during plant-pathogen interaction, specifically in the suppression of plant chitinases that may degrade fungal cell walls through hydrolysis of chitin (Pan et al, 2020;Zhang et al, 2021). For example, the necrotrophic fungi Fusarium oxysporum f. sp.…”
Section: Figure S2 Relative Expression Levels Of Five Pectin Methylte...mentioning
confidence: 99%
“…Moreover, transient expression assays showed that FocM35_1 is secreted into the apoplast and triggers cell death in Nicotiana benthamiana leaves (Zhang et al, 2021). Another M35 protein, RcMEP2 from the polyphagous fungus Rhizoctonia cerealis induces cell death and inhibits the expression of host chitinases when infiltrated into wheat leaves (Pan et al, 2020). The inhibition of plant chitinases represents a fungal strategy to establish successful infections, preserving the integrity of their cell walls and preventing the release of chitin oligomers that trigger the host's immune responses (Sánchez-Vallet et al, 2015).…”
Section: Figure S2 Relative Expression Levels Of Five Pectin Methylte...mentioning
confidence: 99%